Implementation of an agile methodology for data warehouse at the BCP - Marino-Jiménez, Tania (2017)
Nowadays, companies need to make faster decisions, with the support of information technology. Thepresent project, which was applied in the BCP approximately two years ago, consisted in the evaluation and implementation of an agile methodological approach for the development of data warehouse projects, using the Scrum methodology. The work began with a consultancy to identify what improvements and changes would have to be made through a new model of customer service. With the improvement proposals, a pilot was executed to check the effectiveness of the Agile methodology. The benefits were the following: reduction of time to market, reduction of execution time and fulfillment of deadlines in the development stage, availability to attend more requirements, guarantee of the quality of the deliverable due to the constant and active participation of the user, reduction of the risk of error and implementations without value to the business, among other benefits. The model was displayed through the formalization of the process in the organization and an agile governance committee was formed - integrated by the main business managers - to ensure compliance with the model of customer service. As a result of this change, in the project management, the optimization of its costs was achieved.